Tingkat Keterbacaan dan Keefektifan Kalimat pada Teks Narasi sebagai Bahan Ajar Membaca Pemahaman di Buku Narasi Literasi Bahasa Indonesia Kelas IX Terbitan Direktorat Pendidikan - Noufal Azmi Widianto; Riska Amelia Putri; Alifia Diva Juniar; Revania Putri Utami; Fadila Ahammi; Asep Purwo Yudi Utomo; Muslikah Muslikah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Reading comprehension skills are a major focus in Indonesian language learning, especially in grade IX, as narrative comprehension helps students relate information in a broader context. The purpose of this study is to provide comprehensive guidelines for the development of more effective Indonesian learning materials and to strengthen the reading comprehension skills of grade IX students. This study evaluates the readability using Fry's Graph Formula and the effectiveness of sentences in narrative texts as teaching materials for reading comprehension in grade IX Indonesian literacy narrative books. By using the Fry's Graph Formula analysis method, this research helps to adapt the text to the intended grade level. Of the six narrative texts analyzed, there are three that have good readability, two that have poor readability, and one that has poor readability. In addition, this study analyzed sentence ineffectiveness. Sentence ineffectiveness can be caused by various reasons, such as word inefficiency, inaccurate use of conjunctions, inaccuracy in word usage, inaccurate use of punctuation, and meaninglessness. The results of the study provide insight into the quality of grade IX Indonesian literacy narrative teaching materials and contribute to improving students' reading comprehension and ability. The readability and effectiveness of the sentences in the grade IX Indonesian literacy narrative book are very important to ensure that the material presented can be well understood by students, thus having a positive impact on the learning process and the achievement of learning objectives.